2008
DOI: 10.1007/s10608-008-9214-x
|View full text |Cite
|
Sign up to set email alerts
|

The Social Thoughts and Beliefs Scale: Psychometric Properties and its Relation with Interpersonal Functioning in a Non-Clinical Sample

Abstract: Cognitive theorists maintain that maladaptive cognitions play an important role in the formation and maintenance of social anxiety disorder. The Social Thoughts and Beliefs Scale (STABS; Turner et al. Psychol Assessment 15:384-391, 2003) was developed to assess the broad domain of cognitions associated with social anxiety in a clinical sample. The present study with 469 college students examined the applicability of the STABS with a non-clinical sample and its relation with social anxiety symptoms and indice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…It has shown excellent internal consistency, test-retest reliability and discriminant validity [29,30]. Acceptable concurrent validity has also been documented [30]. Chronbach's α for STABS in this study was 0.96.…”
Section: Methodsmentioning
confidence: 55%
See 1 more Smart Citation
“…It has shown excellent internal consistency, test-retest reliability and discriminant validity [29,30]. Acceptable concurrent validity has also been documented [30]. Chronbach's α for STABS in this study was 0.96.…”
Section: Methodsmentioning
confidence: 55%
“…The Social Thoughts and Beliefs Scale (STABS) [29] is a 21-item self-report inventory designed to assess cognition in persons with SP. It has shown excellent internal consistency, test-retest reliability and discriminant validity [29,30]. Acceptable concurrent validity has also been documented [30].…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, Turner et al (2003) found that the STABS is composed of two factors; the first factor is "Social Comparison" and contains beliefs that other people are more socially competent, and the second factor is "Social Ineptness" and contains beliefs related to behaving awkwardly or appearing anxious in social situations. In an undergraduate sample, Fergus et al (2009) confirmed the Social Comparison and Social Ineptness factors of the STABS, and both factors (along with the total STABS score) were positively associated with measures of social anxiety (rs ranged from .63 to .80). Besides the STABS, Rodebaugh (2009) has recently developed the Core Extrusion Schema (CES) measure that assesses the tendency for high socially anxious individuals to conceal aspects of the self due to fear associated with perceived negative evaluation.…”
mentioning
confidence: 58%
“…For example, Beazley et al (2001) found a positive association between social anxiety and negative thoughts (as measured by the Social Interaction Self-Statement Test). Furthermore, Fergus et al (2009) reported a positive association between social anxiety and cognitions that are characteristic of social phobia (as measured by the Social Thoughts and Beliefs Scale).…”
Section: Introductionmentioning
confidence: 99%